2011
DOI: 10.1007/s00299-011-1129-4
|View full text |Cite
|
Sign up to set email alerts
|

Heading date gene, dth3 controlled late flowering in O. Glaberrima Steud. by down-regulating Ehd1

Abstract: Heading date in rice is an important agronomic trait controlled by several genes. In this study, flowering time of variety Dianjingyou 1 (DJY1) was earlier than a near-isogenic line (named NIL) carried chromosome segment from African rice on chromosome 3S, when grown in both long-day (LD) and short-day (SD) conditions. By analyzing a large F2 population from NIL × DJY1, the locus DTH3 (QTL for days to heading on chromosome 3) controlling early heading date in DJY1 was fine mapped to a 64-kb segment which conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Tan et al (2008) cloned the PROG1 gene from common wild rice, and prog1 variants identified in O. sativa disrupt prog1 function and inactivate prog1 expression, leading to erect growth, greater grain number and higher grain yield in cultivated rice. At the same time, the flowering time QTL dth3 , was detected from wild rice species (Bian et al, 2011), and the seed dormancy QTL was also isolated in the genetic populations derived from wild rice species (Gu et al, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Tan et al (2008) cloned the PROG1 gene from common wild rice, and prog1 variants identified in O. sativa disrupt prog1 function and inactivate prog1 expression, leading to erect growth, greater grain number and higher grain yield in cultivated rice. At the same time, the flowering time QTL dth3 , was detected from wild rice species (Bian et al, 2011), and the seed dormancy QTL was also isolated in the genetic populations derived from wild rice species (Gu et al, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…DTH3 up-regulates Ehd1 and RFT1 under both SD and LD conditions and thereby promotes flowering (Bian et al, 2011) (Figure 1). At this QTL, there is functional allelic variation between O. sativa and O. glaberrima , but probably not among O. sativa cultivars.…”
Section: Other Qtgs Underlying Natural Flowering Time Variation In Ricementioning
confidence: 99%
“…S3A). It was reported that the expression level of dth3 in the near isogenic line was lower than that of DTH3 in DJY1, and overexpression of DTH3 caused early flowering (Bian et al, 2011). Probably the polymorphisms in promoter region can cause different gene expression level and resulted functional distinction.…”
mentioning
confidence: 97%
“…QHD2 was mapped to the interval RM497-R240, which contained the recently cloned heading date gene DTH2 (Wu et al, 2013). QHD3 was mapped to the region flanked by markers RM36 and RM232, where DTH3 is located (Bian et al, 2011). No cloned heading date genes were reported in the regions harboring the remaining seven QTLs.…”
mentioning
confidence: 99%